Macroeconomic Factors and Their Relationship with the Composite Stock Price Index (JCI) at IDX - Firman Maulana Fadilah; Ilma Hijrianti; Jamaludin Suhada Shamurti; Junaedi Junaedi; Lisa Kustina (DEAL: International Journal of Economics and Business, 2025)
The purpose of the study was to identify the effect of Inflation, Interest Rates, and Exchange Rates (USD/IDR) on the Composite Stock Price Index (JCI) on the Indonesia Stock Exchange (IDX) during the period 2018-2022. This study uses a quantitative approach and secondary data obtained from the official website of the Indonesia Stock Exchange (IDX). The study population includes all data on inflation, interest rates, rupiah exchange rates, and JCI on the IDX for the period 2018-2022. In determining the sample, the saturated sample method was used using monthly time series data, which resulted in 60 samples. The analysis method applied is multiple linear regression analysis, using Eviews 12 software. The results showed that simultaneously Inflation, Interest Rates, and Exchange Rates (USD/IDR) have a significant influence on the JCI on the IDX. Partially, Inflation has a positive and significant impact on the JCI on the IDX, while Interest Rates and Exchange Rates (USD/IDR) have a negative and significant impact on the JCI on the IDX. These findings imply that policymakers and investors should pay close attention to macroeconomic indicators when making investment or regulatory decisions.